PENGARUH GREEN BRAND KNOWLEDGE , GREEN BRAND POSITIONING DAN ATTITUDE TOWARD GREEN BRAND TERHADAP GREEN PURCHASE INTENTION PADA KONSUMEN AMDK MEREK LE MINERALE Di KOTA SEMARANG - Harminingtyas, Rudika; Susetyarsi, Theresia; Fahlefi, Diva Riza; Prabowo, Catur (JURNAL STIE SEMARANG, 2024)
This research aims to find out whether Green Brand knowledge,Green Brand Positioning, Attitude Toward Green Brand, influence the Green Purchase Intention of bottled drinking water consumers. The independent variables in this research are Green Brand knowledge, Green Brabd Positioning,Attitude Toward Green Brand, . The dependent variable in this research is Green Purchase Intention. The data sources in this research are primary and secondary data, obtained by distributing questionnaires to respondents. The population in this study, namely Aqua Brand AMDK consumers in the city of Semarang, was calculated from the sampling used, namely non- probability sampling. The data analysis method uses the SPSS 23 program. The results show that the Green Brand Knowledge has no significant effect on Green Purchase Intention., This is proven by t-count 1.146 < ttable 1.98580 significance level 0.255 > 0.05. Green Brand Positioning variable has a positive and significant effect on Green Purchase Intention. This is proven by t-count. This is proven by the t-count 4.122 > t-table 1.98580 and a significance level of 0.000 <0.05. Attitude Toward Green Brand has no significant effect on Green Purchase Intention.This is proven by the t-count -0.290 < t-table 1.98580 with a significance level of 0.772 > 0.05 The results of Green Brand Knowledge,Green Brand Positioning Attitude Toward Green Brand, together have a significant effect on Green Purchase Intention. This can be explained by significance level below 5% (α = 0.05) and Fcount 23.961>Ftable 2.70